Displaying uncertainty in the biological reference points of sharks. (November 2015) - Braccini, Matias; Brooks, Elizabeth N.; Wise, Brent; McAuley, Rory
Abstract: Variability in life-history traits influences biological reference points (BRP). For data-poor species such as sharks, BRP have commonly been set at arbitrary values with little consideration of life-history variability. The temperate shark fisheries of Western Australia were used as a case study to develop species-specific limit, threshold and target BRP that consider life history uncertainty and population dynamics. Shark species with higher biological productivity had lower biomass BRP and higher fishing mortality BRP (FBRP ) than less productive species. The interplay of gear selectivity and variability in life history traits influenced BRP uncertainty, particularly for FBRP . Traditionally, stock status is determined by comparing a stock-performance indicator (SPI) to a BRP point estimate based on a set probability of SPI exceeding the point BRP. We proposed an alternative approach where we considered distributions for both SPI and BRP and compared the proportion of overlap between those distributions. In practice, we consider this an improvement to characterizing both uncertainties and an easier-to-grasp concept than a probability of exceeding a point estimate. Highlights: Biological reference points (BRP) and stock performance indicators (SPI) are commonly estimated with error. If management decisions are based on comparing point estimates, the chance of management error can be high. We developed species-specific BRP taking into consideration life history uncertainty and population dynamics. It is important for managers to recognize this uncertainty, so that management action can respond to it appropriately. We proposed a new method for comparing SPI with BRP based on the overlap of their posterior distributions.